Analisis Produk Crowdfunding Lembaga Keuangan Syariah Dalam Menghadapi Dampak Ekonomi Wabah Virus Covid 19 - Yusuf; Siti Pamrih Anjas Wulandari (Tasharruf : Journal of Islamic Economics and Business, 2020)
Growth of technology financial facilitate society in doing monetary transaction way of online for the product of defrayal, fund gathering and also service.. Economic impact which generated by Funnel virus epidemic give opportunity of product of crowdfunding Moslem law expand alternatively fund graving dock. This research aim to to know role of product of crowdfunding Moslem law to natural society of economic impact. This descriptive qualitative research written pursuant at study of literasi. From the results of the study it can be concluded that request of deposit product and defrayal with mutual assistance principle grow productivity model defrayal of Moslem law crowdfunding a period of deceleration of economics, Institute Moslem law technology financial have role to government in balancing economics of side consume and production, Monetary Authority Service needed in the case of observation of activity of institute of financial Moslem law technology to guarantee storey; level trust of society specially economic perpetrator in the case of transaction implementation base on Moslem law and of prudential banking principle exist in Islamic financial institution